Impact of Social Networking Sites on Enhancing English Literacy and Speaking Skills among Selected Students - Mon, Anthony M.; Meer, Jasmine Ayah E.; Edu, Cher Aerice M.; Granada, Hilton Jhun G.; Cortes, Maureen M.; Montejo, Julie P.; Abanes, John Patrick G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
ABSTRACT The advance of technology has provided a third virtual space where people from various regions and linguistic backgrounds can interact with each other regarding social network sites and applica-tions. Therefore, this study aimed to investigate the impact of social media on enhancing English literacy and speaking skills of the Bach-elor of Secondary Education Major in English students of President Ramon Magsaysay State University - Santa Cruz Campus. A quantitative research design was employed to answer the re-search questions. The respondents are female young adults in their second year of study. The findings reveal that the respondents used Facebook, Instagram, TikTok, and Telegram for more than three hours daily, they have strong internet connection for accessing edu-cational content, entertainment, news, and blogs, and strongly agreed that their vocabulary skills in English literacy and speaking were strong, while they agreed on grammar and comprehension skills. There is a significant difference in English literacy and speak-ing skills regarding grammar when grouped by age and year level. Additionally, there is a substantial difference in vocabulary skills when grouped by year level. There is no significant relationship be-tween social media use and the respondents' English literacy and speaking skills. The conclusion of the study has led to the recommendation that the students should be reminded that constant engagement with social media due to their positive attitude may hinder their studies which may lead to poor performance in school meanwhile teachers may incorporate in their classes the use of social media such as giv-ing of assignments and other instructions related to their courses so that their students may not only engage in social media for chatting but also for educational purposes. They should encourage their stu-dents to use the English language on Facebook to improve their Eng-lish language competency.